2017
DOI: 10.1093/aobpla/plw091
|View full text |Cite
|
Sign up to set email alerts
|

Species-environment interactions changed by introduced herbivores in an oceanic high-mountain ecosystem

Abstract: We studied the fitness of an endemic and vulnerable violet species along its altitudinal range (2,400 m - 3,500 m), and we found it to be mainly affected by inter-annual and microhabitat variability along the gradient, especially at the lowest edge. Despite the increasingly adverse environmental conditions, the plant showed no pollen limitation with elevation, which is attributed to the increase in selfing and decrease in competition for pollinators at higher elevations. Plant fitness was extremely reduced owi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
1
7
0
Order By: Relevance
“…Moreover, the selfing rate (approx. 50 %) estimated in this study agrees with the values of autonomous selfing obtained in a previous study (Seguí et al, 2017). Nonetheless, they detected a significant increase in self-fertility with elevation and with intensity of herbivory.…”
Section: Genetic Diversity Of An Endemic Alpine Polyploidsupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, the selfing rate (approx. 50 %) estimated in this study agrees with the values of autonomous selfing obtained in a previous study (Seguí et al, 2017). Nonetheless, they detected a significant increase in self-fertility with elevation and with intensity of herbivory.…”
Section: Genetic Diversity Of An Endemic Alpine Polyploidsupporting
confidence: 92%
“…Nevertheless, following the review by Vekemans and Hardy (2004), our values for the Sp statistics are lower than their estimations according to the biotic traits of V. cheiranthifolia. Sp statistics are expected to be inversely proportional to the density (Heywood, 1991), and it has been found that the damage caused by rabbits in V. cheiranthifolia greatly decreases the plant population densities (Seguí et al, 2017). Moreover, pollen dispersal by insects may be promoting higher outcrossing among individuals within populations, compensating for the selfing effects on the SGS.…”
Section: Genetic Structure and Demographic History Of Populationsmentioning
confidence: 99%
See 3 more Smart Citations